KRITIK TERHADAP SISTEM PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL DI INDONESIA : STUDI UU NO 2 TAHUN 2004 TENTANG PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL PERSPEKTIF TEORI SISTEM HUKUM - Helwan Kasra (SOL JUSTICIA, 2022)
Disputes between workers and employers are often unavoidable, therefore it is necessary to establish a good dispute resolution system. The PPHI Law as a reference in dispute resolution so far has received a lot of criticism. This paper will examine various criticisms of the law so that it can be considered in making improvements to the substance of the law in the future. The research method used in this research is normative legal research. Normative legal research is carried out on primary, secondary and tertiary legal materials as long as they contain legal rules.